Fournier’s Gangrene after Bilateral Vasectomy-A Case Report - Bhattarai, Aabishkar; Karki, Bijaya; Bhandari, Pragya (Birat Journal of Health Sciences, 2020)
Fournier’s gangrene is an acute, rapidly progressing, potentially fatal necrotizing fasciitis affectingthe external genitalia, perineal or perianal regions and is caused by a mixed infection with aerobic/anaerobic bacteria, which commonly affects the men, but can also occur in women and children. The most common foci of infection are from gastrointestinal tract, genitourinary tract or less commonly from the cutaneous injuries. The common risk factors includediabetes mellitus,alcohol abuse, extremes of age, male gender, chronic steroid use, malnutrition and immunosuppression. Uncommonly, Fournier’s gangrene has been documented after vasectomy operation-a permanent technique for male partner sterilization. Here we present a case of Fournier’s gangrene in an adult male who had undergone bilateral standard vasectomy for permanent contraception and presenting after 7 days with gangrene in the scrotum requiring urgent debridement and broad-spectrum antibiotics.